SIFAT PEMESINAN BEBERAPA JENIS KAYU ASAL JAMBI - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Five wood species originated from Jambi were observed for their machining properties in this study. Sawing characteristics (feed speed and surface smoothness) of each species were observed to determine its cutting-ability. Sawn timbers were then cut to sample boards and air-seasoned to approximately 17% moisture content prior to further machining processes. The examined machining properties include planing, shaping, boring, turning and sanding. Examinations were undergone according 10 the modified ASTM D-1666 as firstly described in the Forest Products Research Institute Report No. 160 (1982).Results from this study showed that most of the species could be sawn at medium feed speed with a variation in cutting surface quality, ranging from fair to rough. One species, i.e., rengas pantai (Gluta renghas) is fairly difficult to saw for its irregular (partly interlocked) grain orientation and the abundant deposition of silica (crystals) in its fiber structures. Some species consistently showed good qualities in almost all machining tests, and likely produced excel/en/ surface quality when worked on using sharp culling tools and controlled machining condition. Wood samples tested in wet condition produced a fairly good planing and shaping quality for most wood species. In comparison, however, the air-dried samples significantly revealed a better machining quality. Based on the machining characteristics observed on the five wood species from Jambi, it is recommend able to use rengas tembaga, sumpung and rengas manuk for wood working purposes. Whereas, rengas pantai and kempas are more suitably intended for indoor structural uses.